Synergetic strengthening far beyond rule of mixtures in gradient structured aluminum rod. (September 2016) - Moering, Jordan; Ma, Xiaolong; Malkin, Jacob; Yang, Muxin; Zhu, Yuntian; Mathaudhu, Suveen
Abstract: Gradient structured metals have been reported to exhibit high strength and high ductility. Here we report that the strength of gradient structured aluminum rod is much higher than the value calculated using the rule of mixtures. The mechanical incompatibility in the gradient structured round sample produced 3D stress states, extraordinary strengthening and good ductility. An out of plane 111 wire texture was developed during the testing, which contributes to the evolution of the stress state and mechanical behavior. Graphical abstract: